Factors Influencing the Effectiveness of the Savings-Based Housing Financing Assistance Program in Central Java Province - Devi Setya Ardani; Bambang Hariadi; Imam Subekti (Eduvest - Journal of Universal Studies, 2025)
This study aims to identify the factors influencing the effectiveness of the savings-based housing financing assistance program in Central Java Province. The study uses a quantitative method with data collected through questionnaires distributed to the program recipients. Data analysis was conducted using multiple regression to determine the relationship between independent and dependent variables. The results indicate that household income, education level, access to information, and government support significantly affect the program's effectiveness. Higher household income and better education levels positively contribute to the recipients' ability to save and utilize the housing assistance more effectively. Adequate access to information about the program and procedures, along with strong government support, also enhance the program's effectiveness. These findings suggest that to improve the effectiveness of the savings-based housing financing assistance program, efforts should be made to increase program socialization, improve access to information, and strengthen cooperation between the government and the community.